VD_FINDINFO HC / 2012 / 350 vom 28. März 2012 - VD Tribunal cantonal (2012)
DIVORCE, OBLIGATION D'ENTRETIEN, PERSONNE DIVORCÉE, ENFANT, REVENU HYPOTHÉTIQUE, ACTIVITÉ LUCRATIVE INDÉPENDANTE | 125 al. 1 CC, 125 CC, 285 al. 1 CC, 285 CC